A Study for the Application of Steel Frames on a Traditional Wooden Fishing Boat. (November 2019) - Bochary, L; Firmansyah, M R; Sitepu, G; Asri, S
Abstract: As its main material, specific timbers for supporting boat structure are required in the construction of traditional wooden fishing boat in Indonesia. The requirements for the specific timbers are vary such as it must be water resistant for ship skin planking and must be in the specific form for the boat frames in which the curvature will be different according to the specific curvature of each transversal boat section along the boat length. Currently, the required specific form of timbers for the boat frames are becoming difficult to be acquired especially in the midship area of the ship which requires extreme curvature. The difficulty to acquire the specific curvature form of frames as required have threaten the sustainability of wooden boat construction process in Indonesia. Hence, an alternative material for replacing the wooden material for boat frames is needed. The requirements for the alternative material are as follows; it must be easy to be formed according to the boat transversal section form along the boat length and must be strong enough to support the strength of the wooden boat hull. This research is conducted in order to analyse the feasibility of steel frame application for replacing wooden frame in the construction of traditional wooden fishing boat. Some alternatives of different steel frame dimensions with specific profile forms are analysed to determine the appropriate steel frame construction for certain type of wooden fishing boat. In the end, a recommendation of the steel frame dimensions for replacing wooden frame on a certain traditional wooden fishing boat is proposed.